Answer:
The given expression is factorized as
![4y^2 - 1 = 0 \implies (2y -1)(2y +1) = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zcaog7yxusxxgad77zd5ru18sw0s0dfxek.png)
Explanation:
Here, the given expression to factorize is:
![4y^2 - 1 = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ipefa6jyjy5lpucu59zwn44u7pvt3nsh0n.png)
Now, using Algebraic Identity:
![a^2 - b^2 = (a + b) (a-b)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i1wu801hy8oczy0dk9d8jr4ib2konnitdq.png)
Now here let a = 2y , b = 1
⇒
![(a) ^2 = (2y)^2 = 2y * 2y = 4y^2\\\implies 4y^2 = (2y)^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rfyo99tsfiakzp49qno2tmax0ccg3o4zja.png)
So, The given expression is equivalent to:
![4y^2 - 1 = 0 \implies (2y)^2 - (1)^2 = 0\\\implies (2y -1)(2y +1) = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/eheorz5mdo9jvpvikbgzpenc05lulkcnj9.png)
Hence the given expression is factorized as
![4y^2 - 1 = 0 \implies (2y -1)(2y +1) = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zcaog7yxusxxgad77zd5ru18sw0s0dfxek.png)